EFEKTIVITAS SANKSI ALTERNATIF (KERJA SOSIAL) DALAM KUHP BARU UNTUK TINDAK PIDANA RINGAN: TINJAUAN PUSTAKA COMPARATIF DENGAN PRAKTIK DI NEGARA LAIN - Gunawan Widjaja (INTELIGENSIA MEDIA, 2026)
This study aims to analyse the effectiveness of alternative sanctions in the form of community service under the New Criminal Code (KUHP) (Law No. 1 of 2023) for minor offences, as well as to conduct a comparative literature review of community service practices in other countries. The research method employed is a literature review (library research) using a juridical-normative approach, a statutory approach, a conceptual approach, and a comparative approach. The results of the study indicate that community service under the New Criminal Code has great potential to serve as an effective alternative sanction, as it is designed to be more proportionate, humane, and rehabilitation-oriented compared to short-term imprisonment, whilst also addressing the issue of prison overcrowding. However, its effectiveness cannot be automatically achieved without the support of operational implementing regulations, robust oversight mechanisms, and a structured evaluation system. A comparative review with the Netherlands, the United Kingdom, and Canada shows that the success of community service is highly dependent on the strengthening of probation institutions, a strict monitoring and evaluation system, and coordination between law enforcement agencies and local governments. This study recommends that the central government immediately issue implementing regulations, optimise the role of the Correctional Services Agency, and adopt best practices from the countries under comparison to ensure that community service achieves the intended objectives of sentencing.